Pengaruh Medan Magnetik Eksternal pada Tabung Gas Hidrogen terhadap Spektrum Emisi pada Efek Zeeman - Didik Setyawarno (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2014)
This study aims to know what will happen when the emission line spectrum emitted by gas tube of the hydrogen atom electron at certain wavelength passed in an external magnetic field. This study was analyzed by non quantitaive comparing between without field and with an external magnetic field. Based on the results of research done obtained a result that the emission spectrum of hydrogen gas passed in an external magnetic field changed the intensity of spectrum. The larger intensity of the magnetic field radiated, that shows where the larger magnetic field used the larger distance split of spectral line .